Bendamustine followed by obinutuzumab and venetoclax in chronic lymphocytic leukaemia (CLL2-BAG): primary endpoint analysis of a multicentre, open-label, phase 2 trial. Issue 9 (September 2018) - Cramer, Paula; von Tresckow, Julia; Bahlo, Jasmin; Robrecht, Sandra; Langerbeins, Petra; Al-Sawaf, Othman; Engelke, Anja; Fink, Anna-Maria; Fischer, Kirsten; Tausch, Eugen; Seiler, Till; Fischer von Weikersthal, Ludwig; et al.
Summary: Background: Targeted agents such as the type II anti-CD20 antibody obinutuzumab and the B-cell lymphoma-2 antagonist venetoclax have shown impressive therapeutic activity in chronic lymphocytic leukaemia. The CLL2-BAG trial was initiated to investigate the combination of these two agents in patients with chronic lymphocytic leukaemia. Methods: In this ongoing multicentre, open-label, investigator-initiated phase 2 trial, patients (aged ≥18 years) with chronic lymphocytic leukaemia requiring treatment according to the 2008 International Workshop on Chronic Lymphocytic Leukemia (IWCLL) criteria and an Eastern Cooperative Oncology Group performance status of 0–2 were enrolled at 16 sites in Germany. Patients with a relevant tumour load (absolute lymphocyte count ≥25 000 cells per μL or lymph nodes with a diameter of ≥5 cm) received sequential treatment of debulking with two cycles of bendamustine (70 mg/m 2 intravenously on days 1 and 2 of each of the two 28-day cycles), followed by induction and maintenance with obinutuzumab (1000 mg intravenously on days 1–2, 8, and 15 of the first induction cycle, every 4 weeks in induction cycles 2–6, and every 12 weeks in the maintenance phase) and oral venetoclax (starting in induction cycle 2 with 20 mg/day, with a weekly dose escalation over 5 weeks to the target dose of 400 mg/day). The primary endpoint was the proportion of patients achieving an overall response by investigator assessment at the end of induction treatment. All patients who received at least two induction cycles were included in the efficacy analyses and all patients who received at least one dose of study drug were included in the safety analyses. This study is registered withClinicalTrials.gov, numberNCT02401503 . Findings: Between May 6, 2015, and Jan 4, 2016, 66 patients were enrolled (35 treatment naive and 31 with relapsed or refractory disease), three of whom were excluded from the efficacy analysis because they received fewer than two induction cycles. Of the remaining 63 patients in the efficacy-evaluable population, 34 patients (54%) were treatment naive and 29 (46%) had relapsed or refractory disease. At data cutoff (Feb 28, 2017), all patients had completed induction treatment. At the end of the induction, 60 (95%) of 63 patients (95% CI 87–99) had responded, including all 34 patients in the treatment-naive cohort and 26 [90%] of 29 relapsed or refractory patients. The most common grade 3–4 adverse events during debulking were neutropenia and anaemia (five [11%] of 47 patients each), and thrombocytopenia and infection (three [6%] each). The most common grade 3–4 adverse events during induction were neutropenia (29 [44%] of 66 patients), infection (nine [14%]), thrombocytopenia (eight [12%]), infusion-related reactions (five [8%]), and secondary primary malignancy (four [6%]). 89 serious adverse events, including 69 related to study treatment, were reported. These serious adverse events were also mainly infections (four cases in four patients during debulking and 18 cases in 11 patients during induction) and cytopenia (four cases in four patients during debulking and ten cases in seven patients in induction). Five relapsed or refractory patients died: three cases of sepsis were deemed related to study treatment, whereas two deaths from Richter's transformation were not. Interpretation: The sequential application of bendamustine and obinutuzumab combined with venetoclax caused no unexpected or cumulative toxicities. The high proportion of patients who achieved overall responses, both treatment-naive and relapsed or refractory patients irrespective of physical fitness and genetic risk factors, compare favourably to established chronic lymphocytic leukaemia therapies. Further follow-up will help to define whether the remissions with eradication of minimal residual disease achieved with this combination are durable after treatment discontinuation. Funding: F Hoffmann-La Roche and AbbVie.